2010
DOI: 10.5172/conu.2010.35.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ‘doing’: Supporting clinical leadership and nursing practice in aged care through innovative models of care

Abstract: Contemporary health care environments are increasingly challenged by issues associated with the recruitment and retention of qualified nursing staff. This challenge is particularly felt by residential aged care providers, with registered nurse (RN) numbers already limited and resident acuity rapidly rising. As a result, aged care service providers are increasingly exploring creative and alternative models of care. This article details exploratory research into a pre-existing, alternative model of care in a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 19 publications
1
72
0
Order By: Relevance
“…Venturato and Drew (2010) likewise observe that these terms, while connected, are quite different in meaning. Using the terms interchangeably in the health context, without explanation, has given rise to considerable confusion (Wimpenny, 2002).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Venturato and Drew (2010) likewise observe that these terms, while connected, are quite different in meaning. Using the terms interchangeably in the health context, without explanation, has given rise to considerable confusion (Wimpenny, 2002).…”
mentioning
confidence: 87%
“…Moreover, although connected, those terms have quite different meanings, which create problems when they are used synonymously in research, practice, and policy (Venturato & Drew 2010). Such widespread misuse of the terms has a number of outcomes across health care settings and disciplines, including an undermining of the authenticity of the terms (Davidson et al, 2006;Wimpenny, 2002).…”
Section: Considering the Questionsmentioning
confidence: 99%
“…In the qualitative studies, several traits identified by nursing assistants (NAs) were positively linked to supervisory performance: effective communication skills; respectful demeanor; and demonstrating a competent, loving, and honorable approach (Cooper & Mitchell, 2006;Venturato & Drew, 2010). Other personal qualities that are recognized Figure 1.…”
Section: Structures Related To Supervisory Performancementioning
confidence: 99%
“…Effective supervisors also used a proactive and respectful approach when sharing clinical and nonclinical information with NAs to support them in performing their daily tasks appropriately and preventing complications (Dellefield, 2008;McGillis Hall et al, 2005;McGilton et al, 2009). Charge nurses ensured NAs were "kept in the loop" about information (e.g., organizational policies) required for quality care provision (Venturato & Drew, 2010).…”
Section: Supervisors Provide Support Resources and Informationmentioning
confidence: 99%
“…Two Australian papers link leadership development with innovative practice in the aged care sector [27,28] and Jeon, Merlyn and Chenoweth offer the most extensive literature review of leadership and management in the aged care sector with a 'narrative synthesis' that finally identified 153 publications relevant to the topic of leadership and management and aged care [29]. This study concluded that the literature provided 'ample' evidence of the impact of management and leadership on matters of staff turnover, retention, leave and absenteeism.…”
Section: Nursing Leadership In the Aged Care Environmentmentioning
confidence: 99%